2018
DOI: 10.1111/apt.14564
|View full text |Cite
|
Sign up to set email alerts
|

Microvesicles in hepatic and peripheral vein can predict nonresponse to corticosteroid therapy in severe alcoholic hepatitis

Abstract: SummaryBackground: Severe alcoholic hepatitis patients have high mortality and limited

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 27 publications
(53 reference statements)
0
20
0
Order By: Relevance
“…Alternatively, high circulating levels of bacterial DNA may predict the development of infection within the first 7 days of corticosteroid therapy and identify non‐responders . A further study found that circulating microvesicles, reflective of oxidative stress, are more numerous and larger in patients with a Lille non‐response as are higher levels of urinary albumin . Higher levels of lipopolysaccharide, procalcitonin and the presence of the systemic inflammatory response syndrome (SIRS) have also been shown to indicate a worse outcome at 90 days in corticosteroid treated patients .…”
Section: Discussionmentioning
confidence: 97%
“…Alternatively, high circulating levels of bacterial DNA may predict the development of infection within the first 7 days of corticosteroid therapy and identify non‐responders . A further study found that circulating microvesicles, reflective of oxidative stress, are more numerous and larger in patients with a Lille non‐response as are higher levels of urinary albumin . Higher levels of lipopolysaccharide, procalcitonin and the presence of the systemic inflammatory response syndrome (SIRS) have also been shown to indicate a worse outcome at 90 days in corticosteroid treated patients .…”
Section: Discussionmentioning
confidence: 97%
“…Test performances were higher when total fragments were assessed and when using a diagnostic algorithm, diagnostic accuracy reached 81%. Sukriti et al analysed EV population in peripheral and hepatic vein blood obtained from patients with severe alcoholic hepatitis treated with corticosteroid . At admission, blood counts of CD3+/CD4+ (T‐cell origin), CD68+/CD11b+ (macrophage origin), CD34+ (hematopoietic stem cells) and ASGPR+ (hepatocytes) EV were higher in non‐responders compared to patient who did respond to steroid therapy, whereas neutrophil‐ and natural killer cell EV counts remained unchanged.…”
Section: Extracellular Vesicles In Chronic Liver Diseasesmentioning
confidence: 89%
“…The collected EVs were confirmed and characterized using different size latex beads using flow cytometer. Detailed protocol described previously and in Data . However, the presence of other types of vesicles cannot be excluded, and we have therefore referred to the isolated vesicles as extracellular vesicles.…”
Section: Methodsmentioning
confidence: 99%